PENGEMBANGAN MODUL INTEGRATIF PADA MATERI PUASA DI MTS NEGERI 11 TANAH DATAR - Daswati, Daswati; Trisoni, Ridwal; Roza, Yanti Mulia; Fadriati, Fadriati; Gustina, Gustina; Munir, Sirajul (Penerbit Widina, Widina Media Utama, 2025)
Students at MTs Negeri 11 Tanah Datar had difficulty understanding the fasting material because the textbook used had complex language, long sentences, and uninteresting presentation, consisting only of text with few pictures. This caused students to be less enthusiastic about learning, and their learning outcomes only reached 50% of the mastery level, indicating a problem in the effectiveness of learning. This study used the research and development (RD) method with the 4-D model (Define, Design, Develop, Disseminate) to develop an integrative module on fasting material at MTs Negeri 11 Tanah Datar. The aim was to produce an effective, interesting learning module that suited the students' needs, particularly in improving their understanding of fasting material. The results of this study indicate that this research has produced an integrative module on fasting material for eighth-grade students at MTs Negeri 11 Tanah Datar. The module was developed using the 4-D model (Define, Design, Develop, Disseminate) with a focus on an integrative approach that combines aspects of fiqh, health, social, and environmental issues. Expert validation results show that the module is highly valid (85%) with aspects of presentation, language, and content that meet standards. Practicality tests by students also show that the module is highly practical (88%) with an appearance, content, language, and usage that are easy to understand. This module is expected to improve student understanding and become an interesting and effective learning solution. The module is disseminated digitally through platforms such as Google Drive and WhatsApp to ensure wide and easy access.ABSTRAKSiswa di MTs Negeri 11 Tanah Datar mengalami kesulitan dalam memahami materi puasa karena buku paket yang digunakan memiliki bahasa yang kompleks, kalimat yang panjang, dan penyajian yang tidak menarik, hanya berupa tulisan dengan sedikit gambar. Hal ini menyebabkan siswa kurang antusias dalam belajar, dan hasil belajar mereka hanya mencapai 50% tingkat ketuntasan, menandakan adanya masalah dalam efektivitas pembelajaran. Penelitian ini menggunakan metode research and development (RD) dengan model 4-D (Define, Design, Develop, Disseminate) untuk mengembangkan modul integratif pada materi puasa di MTs Negeri 11 Tanah Datar. Tujuannya adalah menghasilkan modul pembelajaran yang efektif, menarik, dan sesuai dengan kebutuhan siswa, khususnya dalam meningkatkan pemahaman materi puasa. Hasil penelitian menjukkan, bahwa penelitian ini menghasilkan modul integratif pada materi puasa untuk siswa kelas VIII MTs Negeri 11 Tanah Datar. Modul dikembangkan menggunakan model 4-D (Define, Design, Develop, Disseminate) dengan fokus pada pendekatan integratif yang menggabungkan aspek fikih, kesehatan, sosial, dan lingkungan. Hasil validasi ahli menunjukkan modul sangat valid (85%) dengan aspek penyajian, bahasa, dan isi yang memenuhi standar. Uji praktikalitas oleh siswa juga menunjukkan modul sangat praktis (88%) dengan tampilan, isi, bahasa, dan penggunaan yang mudah dipahami. Modul ini diharapkan dapat meningkatkan pemahaman siswa dan menjadi solusi pembelajaran yang menarik serta efektif. Penyebaran modul dilakukan secara digital melalui platform seperti Google Drive dan WhatsApp untuk memastikan akses yang luas dan mudah.